Neolithic settlement and paleopedological changes during the Middle Holocene in northern Sardinia (Italy) - Marras, Gian Battista; Boschian, Giovanni (Frontiers in Environmental Archaeology, 2023)
Sardinia is the second biggest island in the Mediterranean region and has been intensely settled since the Middle Holocene (c.7750 BP). Despite a large number of documented Neolithic archaeological sites, very little is known about human-environmental interactions, including land use and domestic activities associated with the emergence and expansion of Neolithic settlements (c. 7750 and 5500 BP). To shed new light on these issues, we carried out new geoarchaeological analyses on buried soils and archaeological sequences exposed at the Neolithic site of Contraguda, northern Sardinia. Physical-chemical analyses combined with a micromorphological study of 24 thin sections from archaeological deposits and buried soil horizons were performed to evaluate the formation processes of archaeological deposits and paleosols. Soil micromorphology detected the presence of pedofeatures originating from land clearance and agricultural activities from the buried Vertisol. Vertisol and Entisol formation largely resulted from the anthropic impact on the landscape, which changed the trajectories of soil development and caused desertification of the environment. Furthermore, sediment fabric and pedofeatures also allowed us to reconstruct Neolithic domestic practices, showing that household maintenance waste debris, which also included animal penning refusal, was dumped into pit structures. Together, our results provide the first geoarchaeological evidence of human impact on soil development within the island during the Middle Holocene and give new insight into the Middle Neolithic (c. 6500-6000 BP) domestic behaviour and land use activities. These findings have significant implications for understanding the island's pedological history and offer a valuable insight on the settlement organization of the Neolithic farming communities and their impacts on the paleoenvironment of Sardinia.